The roles of peace and security, political leadership, and entrepreneurship in the socio-economic development of emerging countries : a compendium of lessons learnt from sub-saharan Africa - Adu-Amanfoh, Francis (Bloomington, IN : Authorhouse, 2014)
"Shows how the works of contemporary global security and political analysts, and experiences from today's highly industrialized nations, conclude that the existence of peace and security, effective and exemplary political leadership, and sustained entrepreneurship are critical ingredients and catalysts for national socio-economic development. Certainly, these ingredients have helped in building the nations of the 'developed world, ' but how can these ingredients help the nations of the 'emerging world'? This book searches for a response and lessons to be learnt. Hence, the purpose of the book, essentially, is to examine the roles that peace and security, political leadership, and entrepreneurship can play in the sustainable socio-economic development of emerging countries, exemplified by sub-Saharan Africa. The book first reviews the nature of the 'emerging world', discusses the subject matter in detail, and concludes with a compendium of lessons to be learnt by, primarily, political leaders, national security practitioners, entrepreneurs and investors, and academicians"--Faduamanfoh website.
Includes bibliographical references and index.
Keywords: Economic development -- Political aspects -- Africa, Sub-Saharan.; National security -- Economic aspects -- Africa, Sub-Saharan.; Peace-building -- Economic aspects -- Africa, Sub-Saharan.; Economic history; National security -- Economic aspects; Peace-building -- Economic aspects; Africa, Sub-Saharan -- Economic conditions